IMPLEMENTASI ANGGARAN BERBASIS KINERJA DI INDONESIA - Kuntaryanto, Oki (Kiat Bisnis, 2013)
Performance based budgeting is an answer to old style budgeting which is traditional budgeting. Due to its benefits, many countries implement this kind of budgeting system. Indonesia is also a country which tries to implement this budgeting system as a replacement for traditional budgeting. However, the implementation of budgeting system creates several controversies. This article tries to investigate the implementation of performance based budgeting in Indonesia. By using literature study, this article investigates the implementation of performance based budgeting in several public entities in Indonesia, both central government entities and local government entity. The entities to be investigated are: Sekretariat Negara (State Secretariat), Direktorat Jenderal Perbendaharaan Negara (State Treasurer), Kabupaten Tanah Datar (The Regency of Tanah Datar), central government entities, and state university. The results imply that implementation of performance based budgeting still experiences some constraints which are typical. The first constraint is the problem how to link between funding and performance indicator which most entities put focus too much on the link between them. The second constraint comes from the involvement of parliament which is too focus on political vested interest. The third constraint lies on the limitation of human resource. Keywords: performance based budgeting, perormance, budgeting, government, indicator